The Effect of Changing the Value of Currency Upon Fulfillment of Debt - Heravi, Farid Ahmad (Journal of Social Sciences - Kabul University, 2023)
Fluctuation the value of money is one of the hazardous financial phenomena that has challenged the economy of countries. In some Islamic countries, due to consecutive wars and political and climatic changes, there has been a sudden change in the value of currency; Because they are idiomatic money and are exposed to fluctuations, as it creates some serious Shari'a queries regarding the fulfillment of debt by banknotes particularly in the case of value decline; so, the early and contemporary jurists commented in this context, that in the payment of gold, silver, fungibles and coins money it is necessary to pay the same according to the consensus of all jurists, except in the case of coin money, the students of Abu Hanifahn and some other sects consider it necessary to pay the value. In term of banknotes are also required to be paid the same in point of contemporary jurists and legal scholars, except for the students of Imam Abu Hanifah and some contemporaries, payment of value is required. The student of Imam Abu Hanafa opinion is preferable because it can solve financial problems better.